2017
DOI: 10.1021/acs.chemmater.6b05353
|View full text |Cite
|
Sign up to set email alerts
|

From Nano- to Micrometer Scale: The Role of Antisolvent Treatment on High Performance Perovskite Solar Cells

Abstract: To date, antisolvent treatment has become one of the most important means to fabricate high efficiency perovskite solar cells (PSCs); however, the few reported antisolvents have not been analyzed on a uniform platform, and there is hitherto no clear reasoning in the choice of antisolvents toward high performance PSCs. Here, we study the role of the antisolvents in the nucleation kinetics of perovskite solutions and their residual influence on perovskite crystal growth, film formation, and device performance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
230
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(246 citation statements)
references
References 31 publications
(51 reference statements)
9
230
0
Order By: Relevance
“…Based on these results, we conclude that the major effect of CB dripping is to induce the nucleation of the MA 3 Bi 2 I 9 phase directly from the ink, which in turn solidifies the MA 3 Bi 2 I 9 layer during solution casting. This has been shown to be due to the solubility of GBL and DMSO solvents in CB, which helps their rapid extraction from the solution‐cast film . In contrast, the as‐cast film remains partially solvated with DMSO and GBL, which take much longer to leave, thanks in part to interactions with the solute and their low vapor pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, we conclude that the major effect of CB dripping is to induce the nucleation of the MA 3 Bi 2 I 9 phase directly from the ink, which in turn solidifies the MA 3 Bi 2 I 9 layer during solution casting. This has been shown to be due to the solubility of GBL and DMSO solvents in CB, which helps their rapid extraction from the solution‐cast film . In contrast, the as‐cast film remains partially solvated with DMSO and GBL, which take much longer to leave, thanks in part to interactions with the solute and their low vapor pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Paek et al. used toluene as an antisolvent whereas chlorobenzene was chosen as antisolvent by Xiao et al . Cho et al.…”
Section: Perovskite‐based Ledsmentioning
confidence: 99%
“…We should also notice here that DE produced significantly lower PCEs when compared to rival CB and TL. Finally, the authors suggested a good trick to see whether an antisolvent is good or bad: one injects the anti-solvent in a vial containing the precursor solution; the formation of the perovskite crystal (brown-blackish precipitate) can be a promising sign for high efficiencies (Figure 11b) [70].…”
Section: Various Anti-solvents Dripping Combined With Adduct Methodsmentioning
confidence: 99%